Efek Arus Berlebih Proteksi Katodik Terhadap Penurunan Kekuatan Lekatan Antara Baja Tulangan dan Beton - Kristianto, Anang; Imran, Iswandi; Purwadaria, Sunara (Universitas Kristen Maranatha, 2003)
The results of a study on the effect of overcurrent on the bond strength between reinforcing steel and concrete are presented in this paper. Cathodic protection with a constant current density, based on the surface area of reinforcing steel, was applied to the test specimens for 5 months. A chloride mixture of 1.5% and 3.0% by weight of cement was added to the concrete mix in the form of CaCl2, to analyze the effect of CaCl2, and chloride concentration on the bond strength of reinforcing steel and concrete when cathodic protection current was applied. In this study, it was found that excessive current flowing into reinforcing steel resulted in a decrease in the bond strength between reinforcing steel and concrete. The decrease in bond strength in normal concrete (without CaCl2 admixture) was 4.33%, 9.63%, 13.29%, and 25.93% for current densities of 40, 200, 500, and 1000 mA/m2, respectively. In specimens with a mixture of CaCl2, 1.5%, there was an increase in adhesion strength of up to 108% for the protective current density, but at excess current density there was a decrease of up to 45.2%. SEM-EDS test results also showed a significant accumulation of Na and K and a reduction of chloride around the reinforcing steel. The formation of Na and K at the interface of reinforcing steel and concrete causes softening of the concrete which results in a decrease in the bond strength between reinforcing steel and concrete.